THE EFFECT OF IMPLEMENTING GCG (GOOD CORPORATE GOVERNANCE), WITH GGE (GREEN-GROWTH ECONOMY) AS A MODERATING VARIABLE OF FINANCIAL PERFORMANCE ON INCREASING ECONOMIC INCOME THROUGH GDP/GNP POST-TOWARDS THE NEW NORMAL - Prihatiningsih, Margaretha; Subagyo, Yusup Hari; Sibarani, Elisabeth Francisca; Paska, Intan; Ikko, Felix (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Research with the title: